2011
DOI: 10.5897/ajpp11.590
|View full text |Cite
|
Sign up to set email alerts
|

Phytoconstituent screening and antimicrobial principles of leaf extracts of two variants of Morus alba (S30 and S54)

Abstract: Efficacies of the two variants of Morus alba locally grown in Forestry ResearchInstitute of Nigeria, were investigated following the recommended procedure of analysis. Phytochemical, proximate and mineral compositions of M. alba leaves were determined using a standard procedure. Antimicrobial properties of leaf extracts of M. alba were also investigated against laboratory standards of both bacteria and fungi using the disc diffusion method. Phytochemical screening showed the presence of saponins, alkaloids, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In this study kuwanon G was separated from methanolic extract of white mulberry and it showed antimicrobial activity with minimum inhibitory concentrations (MICs) of 8.0 µg/mL against Streptococcus mutans that is responsible for dental caries. In the experiment all the ethanolic extracts were found active which gets similarity with Ayoola et al [20] who evaluated the antibacterial and antifungal activity of phytoconstituents isolated from the aqueous and ethanolic (99.7% v/v) extract of white mulberry. The study concluded that white mulberry extracts can be able to treat bacterial and fungal infections and these activities are due to the presence of phytochemicals, minerals.…”
Section: Discussionsupporting
confidence: 68%
“…In this study kuwanon G was separated from methanolic extract of white mulberry and it showed antimicrobial activity with minimum inhibitory concentrations (MICs) of 8.0 µg/mL against Streptococcus mutans that is responsible for dental caries. In the experiment all the ethanolic extracts were found active which gets similarity with Ayoola et al [20] who evaluated the antibacterial and antifungal activity of phytoconstituents isolated from the aqueous and ethanolic (99.7% v/v) extract of white mulberry. The study concluded that white mulberry extracts can be able to treat bacterial and fungal infections and these activities are due to the presence of phytochemicals, minerals.…”
Section: Discussionsupporting
confidence: 68%
“…Results on total phytic acid obtained by various, mostly colorimetric methods from different laboratories are difficult to compare. The quantification by spectrophotometry has its shortcomings, and values for foliage are rarely published, but are an order of magnitude apart (very low; very high; variable). No reference values for herbage were found for the method we applied, which is a standard method for phytates in common bean grains at the International Center for Tropical Agriculture, although it is similar to the one for weeds used by Gutierrez et al Even regarding the high standard deviation among replicates, the phytic acid concentration in the forages was in general much higher than in Phaseolus grains, and also in grains of the same Vigna unguiculata accession, which was analyzed as herbage (Torres J, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…The use of medicinal plants as a source for relief from illness is doubtless an art as old as mankind [ 7 ]. Plants are the richest resource of drugs of traditional systems of medicine, modern medicines, nutraceuticals, food supplements, folk medicines, pharmaceutical intermediates and chemical entities for synthetic drugs [ 8 ]. Plants have been known to synthesize a variety of compounds to protect themselves against a variety of their own pathogens and, therefore, can be considered as potential source of different classes of antimicrobial substances [ 6 ].…”
Section: Introductionmentioning
confidence: 99%